Determinan Pembiayaan Murabahah Dan Non Performing Financing Studi Pada Bank Umum Syariah Di Indonesia - Sichke Dila Putri; Supami Wahyu Setiyowati (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to analyze the effect of DPK, FDR, and CAR on Murabahah Financing and also the effect of FDR and CAR on Non-Performing Financing at Islamic Commercial Banks registered with OJK for the 2017-20201 period. Of the 15 BUS, 8 BUS were obtained as research samples using a purposive sampling technique. Partial Least Square is used as a data analysis tool in this study. With the results of the study showing that third party funds have a negative effect on murabahah financing, Financing to Deposit Ratio has a negative effect on murabahah financing, Capital Adequacy Ratio has a positive effect on murabaha financing, Financing to Deposit Ratio has no effect on Non Performing Financing, Capital Adequacy Ratio has a negative effect towards Non-Performing Financing. From the results of the study it can be concluded that in order to increase Murabahah Financing and maintain the stability of the bank's NPF it is necessary to pay attention to third party funds, the Financing to Deposit Ratio and the Capital Adequacy Ratio.